RGMb is a novel binding partner for PD-L2 and its engagement with PD-L2 promotes respiratory tolerance - Xiao, Yanping; Yu, Sanhong; Zhu, Baogong; Bedoret, Denis; Bu, Xia; Francisco, Loise M; Hua, Ping; Duke-Cohan, Jonathan S; Umetsu, Dale T; Sharpe, Arlene H; DeKruyff, Rosemarie H; Freeman, Gordon J (The Journal of experimental medicine, 2014)
We report that programmed death ligand 2 (PD-L2), a known ligand of PD-1, also binds to repulsive guidance molecule b (RGMb), which was originally identified in the nervous system as a co-receptor for bone morphogenetic proteins (BMPs). PD-L2 and BMP-2/4 bind to distinct sites on RGMb. Normal resting lung interstitial macrophages and alveolar epithelial cells express high levels of RGMb mRNA, whereas lung dendritic cells express PD-L2. Blockade of the RGMb-PD-L2 interaction markedly impaired the development of respiratory tolerance by interfering with the initial T cell expansion required for respiratory tolerance. Experiments with PD-L2-deficient mice showed that PD-L2 expression on non-T cells was critical for respiratory tolerance, but expression on T cells was not required. Because PD-L2 binds to both PD-1, which inhibits antitumor immunity, and to RGMb, which regulates respiratory immunity, targeting the PD-L2 pathway has therapeutic potential for asthma, cancer, and other immune-mediated disorders. Understanding this pathway may provide insights into how to optimally modulate the PD-1 pathway in cancer immunotherapy while minimizing adverse events.